Characteristics of Egg White Effervescent Tablet with Different Effervescent Mix Concentration (Jurnal Ilmu dan Teknologi Hasil Ternak, 2021)
Egg white is one source of protein that has many functions, including as an antimicrobial, antihypertensive, anti-cancer, and this can also be used as a preservative and sweetener. The addition of egg white powder to effervescent tablets with lemon essence is expected to increase protein levels in the tablet. The purpose of this study was to study the physical, chemical and organoleptic characteristics of effervescent tablets by adding egg white powder to the formulation. The study design used a randomized block design (RBD) with the making period as a group. The treatments used were different concentrations of effervescent mix (sodium bicarbonate, citric acid and tartaric acid), that is, 55, 60 and 65%. Data from the test results were tested with analysis of variance (ANOVA), further tests with the Duncan test. The physical characteristics of effervescent tablets with the addition of egg white powder and the difference in the concentration of effervescent mix as a treatment were not significantly different among treatments. The chemical characteristics of egg white effervescent tablets did not change with the treatment concentration of effervescent mix 55, 60 and 65% but the water activity (aw) of the effervescent tablets changed. Increasing the concentration of effervescent mix treatment can reduce the value of aw from 0.58 to 0.50. The addition of albumen powder with different concentrations of effervescent mix resulted in effervescent tablets according to predetermined standards. The organoleptic test results on the overall assessment of egg white powder effervescent tablets were somewhat favorable